Contrast‐Enhanced Sonographically Guided Percutaneous 915‐MHz Microwave Ablation Therapy Compared to Local Hemostatic Drug Injection in a Renal Artery Injury Model. (1st April 2014) - Zhang, Guoming; Dong, Lei; Tai, Yanhong; Sun, Yuanyuan; Liang, Ping; Liu, Xiaohong; Wang, Hui; Zhang, Yan; Shen, Hong; Sun, Na
Abstract : Objectives: The purpose of this study was to show the contrast‐enhanced sonographic features of various levels of renal artery rupture and to validate the therapeutic effects of percutaneous 915‐MHz microwave ablation compared to hemostatic drug injection (batroxobin) using an in vivo canine renal artery injury model. Methods: Three renal artery hemorrhage models (A, diameter <1 mm, subcapsular artery; B, diameter 1–2 mm, interlobar artery; and C, diameter 2–3 mm, segmental artery) were created in 24 canines for this study. Contrast‐enhanced sonography was used to show the bleeding features and guide hemostatic therapies using 915‐MHz microwave ablation and local batroxobin injection. Success rates were assessed according to amounts of bleeding, times required for hemostatic action, and volumes of fluid infusion required using pathologic examination as a reference standard. Results: Contrast‐enhanced sonography clearly showed renal artery ruptures with active bleeding at various levels and degrees and was very useful to make diagnoses and guide therapies. The success rate in the microwave treatment group was higher than that in the drug injection group (except group A; P < .05). The time required for hemostasis and the volume of fluid infusion required in the microwave group were notably less than those in the drug injection group ( P < .05). Conclusions: Contrast‐enhanced sonography is a useful imaging method for assessing renal vessel injury and guide interventional therapies. Contrast‐enhanced sonographically guided percutaneous 915‐MHz microwave ablation is a preferred hemostatic technique for treatment of renal artery injury, with greater effectiveness and less tissue damage compared to local drug injection.